Neuropsychopharmacology of JNJ-55308942: evaluation of a clinical candidate targeting P2X7 ion channels in animal models of neuroinflammation and anhedonia. (December 2018) - Bhattacharya, Anindya; Lord, Brian; Grigoleit, Jan-Sebastian; He, Yingbo; Fraser, Ian; Campbell, Shannon; Taylor, Natalie; Aluisio, Leah; O'Connor, Jason; Papp, Mariusz; Chrovian, Christa; Carruthers, Nicholas; et al.
Abstract Emerging data continues to point towards a relationship between neuroinflammation and neuropsychiatric disorders. ATP-induced activation of P2X7 results in IL-1β release causing neuroinflammation and microglial activation. This study describes the in-vitro and in-vivo neuropharmacology of a novel brain-penetrant P2X7 antagonist, JNJ-55308942, currently in clinical development. JNJ-55308942 is a high-affinity, selective, brain-penetrant (brain/plasma of 1) P2X7 functional antagonist. In human blood and in mouse blood and microglia, JNJ-55308942 attenuated IL-1β release in a potent and concentration-dependent manner. After oral dosing, the compound exhibited both dose and concentration-dependent occupancy of rat brain P2X7 with an ED50 of 0.07 mg/kg. The P2X7 antagonist (3 mg/kg, oral) blocked Bz-ATP-induced brain IL-1β release in conscious rats, demonstrating functional effects of target engagement in the brain. JNJ-55308942 (30 mg/kg, oral) attenuated LPS-induced microglial activation in mice, assessed at day 2 after a single systemic LPS injection (0.8 mg/kg, i.p.), suggesting a role for P2X7 in microglial activation. In a model of BCG-induced depression, JNJ-55308942 dosed orally (30 mg/kg), reversed the BCG-induced deficits of sucrose preference and social interaction, indicating for the first time a role of P2X7 in the BCG model of depression, probably due to the neuroinflammatory component induced by BCG inoculation. Finally, in a rat model of chronic stress induced sucrose intake deficit, JNJ-55308942 reversed the deficit with concurrent high P2X7 brain occupancy as measured by autoradiography. This body of data demonstrates that JNJ-55308942 is a potent P2X7 antagonist, engages the target in brain, modulates IL-1β release and microglial activation leading to efficacy in two models of anhedonia in rodents.